2010
DOI: 10.3168/jds.2010-3104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 times daily milking during early versus full lactation of Holstein cows on milk production and blood metabolites

Abstract: An experiment was conducted to determine the effects of different milking frequencies on entire lactation production performance in Holstein cows. One hundred twenty Holstein cows were assigned to 3 milking treatments (35 multiparous and 5 primiparous cows in each): 1) milking 6 times daily for the entire lactation (6x); 2) milking 6 times daily for the first 90 d in milk (DIM) and switching to 3 times daily milking afterward (6x-3x); and 3) milking 3 times daily for the entire lactation (3x). Milk yield was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…older cows) are less responsive to frequent milking. A similar assumption was made by Eslamizad et al (2010).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…older cows) are less responsive to frequent milking. A similar assumption was made by Eslamizad et al (2010).…”
Section: Discussionsupporting
confidence: 63%
“…These results might prove the hypothesis that a narrow window exists after calving when the mammary gland is responsive to frequent milking (Wall and McFadden, 2008). The duration of 21 days after calving seems to be sufficient because a longer duration of HMF, 42 or 90 days (Bar-Peled et al, 1995;Eslamizad et al, 2010), did not have any additional effect on milk yield. A few other studies demonstrated that an even shorter HMF period (1 to 14 or 7 to 21 days) might have a persistent effect similar to that found in this study with a 21-day period (Hale et al, 2003;Dahl et al, 2004;Wall and McFadden, 2007).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations